PERFORMANCE OF GLADIOLUS CULTIVARS UNDER OPEN FIELD CONDITIONS FOR VEGETATIVE AND CORM PARAMETERS IN SOUTHERN ZONE OF ANDHRA PRADESH - AVILALA, DEVI PRIYA; LAKSHMI, K. SWARAJYA; R. NAGARAJU; REDDY, D. SRINIVASA (The Bioscan, 2018)
A field experiment was carried out among fourteen cultivars of gladiolus to find out the suitable cultivar under Southern zone of Andhra Pradesh for Vegetative and corm parameters. There was significant differences among varieties with respect to vegetative and corm parameters. Among different cultivars Bindya recorded maximum plant height at spike emergence (80.27 cm) and at spike harvest (110.33 cm), maximum number of leaves plant1 (9.46), leaf length (58.33 cm) and leaf width (3.79 cm), maximum weight of corms plant-1 (126.13 g) and diameter of corm (7.71 cm). Cultivar American Beauty (2.60) and Arka Amar (2.47) recorded maximum number of corms plant-1. Cultivar Arka Amar produced more number of cormels plant-1 (34.33). The weight of cormels was highest in cultivar Sylvia (40.69 g) and Arka Amar (38.45 g). From the present investigation it was concluded that the gladiolus cultivars Bindya, American Beauty and Arka Amar were found promising for corm and cormel yield.